Crossing the divide: a longitudinal study of effective treatments for people with autism and attention deficit hyperactivity disorder across the lifespan - Declan Murphy; Karen Glaser; Hannah Hayward; Hanna Eklund; Tim Cadman; James Findon; Emma Woodhouse; Karen Ashwood; Jennifer Beecham; Patrick Bolton; Fiona McEwen; Ellie Wilson; et al. (NIHR Journals Library, 2018)
Background: Autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD) frequently persist into adolescence and young adulthood. However, there are few clinical services that support those with these disorders through adulthood. Objective: Our aim was to determine if clinical services meet the needs of people with ASD and ADHD, who are 'at transition' from childhood to adulthood. Design: A longitudinal study of individuals with ASD and ADHD, the impact of services and treatments. Methods: Our research methods included (1) interviewing > 180 affected individuals (and their families) with a confirmed diagnosis of ASD and/or ADHD, (2) screening for ASD and ADHD in approximately 1600 patients and (3) surveying general practitioner prescribing to 5651 ASD individuals across the UK. In addition, we tested the effectiveness of (1) new ASD diagnostic interview measures in 169 twins, 145 familes and 150 non-twins, (2) a magnetic resonance imaging-based diagnostic aid in 40 ASD individuals, (3) psychological treatments in 46 ASD individuals and (4) the feasability of e-learning in 28 clinicians. Setting: NHS clinical services and prisons. Participants: Focus - young people with ASD and ADHD as they 'transition' from childhood and adolescence into early adulthood. Interventions: Testing the utility of diagnostic measures and services, web-based learning interventions, pharmacological prescribing and cognitive-behavioural treatments. Main outcome measures: Symptom severity, service provision and met/unmet need. Results: People with ASD and ADHD have very significant unmet needs as they transition through adolescence and young adulthood. A major contributor to this is the presence of associated mental health symptoms. However, these are mostly undiagnosed (and untreated) by clinical services. Furthermore, the largest determinant of service provision was age and not severity of symptoms. We provide new tools to help diagnose both the core disorders and their associated symptoms. We also provide proof of concept for the effectiveness of simple psychological interventions to treat obsessional symptoms, the potential to run treatment trials in prisons and training interventions. Limitations: Our findings only apply to clinical service settings. Conclusions: As individuals 'transition' their contact with treatment and support services reduces significantly. Needs-led services are required, which can both identify individuals with the 'core symptoms' of ASD and ADHD and treat their residual symptoms and associated conditions. Future work: To test our new diagnostic measures and treatment approaches in larger controlled trials. Trial registration: Current Controlled Trials ISRCTN87114880. Funding: The National Institute for Health Research Programme Grants for Applied Research programme.